Physics Learning using Constructivism Approach in Palembang High School - Maulia, Nursanti; Widayatsih, Tri (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2023)
The goal of this research is to produce education that is more meaningful. To achieve this goal, it is important to select media and educational strategies that can help students truly understand and participate fully in the teaching and learning process. In order to encourage students to think and understand the subject matter rather than just hear, receive, and remember it, as well as to be able to develop students’ thinking abilities in achieving learning outcomes, the researcher chose constructivism education that was centered on students. This educational approach of constructivism was applied in pairs. the greatest. With a sequential exploratory design, this research is a type of qualitative and quantitative research in which qualitative methods are used in the first stage and quantitative methods in the second. The research information was gathered through observations, interviews, documentation, and exams to gauge the physics knowledge of the students and the success of this study. According to the research findings, there are variations between the pre-test and post-test learning outcomes for the experimental class employing the constructivism approach in physics teaching. Based on the outcomes, it can be concluded that the educational paradigm employed, particularly the constructivism method, produces superior outcomes.